Spatial Complexity in Dissolved Organic Matter and Trace Elements Driven by Hydrography and Freshwater Input Across the Arctic Ocean During 2015 Arctic GEOTRACES Expeditions. Issue 11 (4th November 2022) - Williford, Tatiana; Amon, Rainer M. W.; Kaiser, Karl; Benner, Ronald; Stedmon, Colin; Bauch, Dorothea; Fitzsimmons, Jessica N.; Gerringa, Loes J. A.; Newton, Robert; Hansell, Dennis A.; Granskog, Mats A.; Jensen, Laramie; et al.
Abstract: This study traces dissolved organic matter (DOM) in different water masses of the Arctic Ocean and its effect on the distributions of trace elements (TEs; Fe, Cu, Mn, Ni, Zn, Cd) using fluorescent properties of DOM and the terrigenous biomarker lignin. The Nansen, Amundsen, and Makarov Basins were characterized by the influence of Atlantic water and the fluvial discharge of the Siberian Rivers with high concentrations of terrigenous DOM (tDOM). The Canada Basin and the Chukchi Sea were characterized by Pacific water, modified through contact with productive shelf sediments with elevated levels of marine DOM. Within the surface layer of the Beaufort Gyre, meteoric water (river water and precipitation) was characterized by low concentrations of lignin and tDOM fluorescence proxies as DOM is removed during freezing. High‐resolution in situ fluorescence profiles revealed that DOM distribution closely followed isopycnals, indicating the strong influence of sea‐ice formation and melt, which was also reflected in strong correlations between DOM fluorescence and brine contributions. The relationship of DOM and hydrography to TEs showed that terrigenous and marine DOM were likely carriers of dissolved Fe, Ni, Cu from the Eurasian shelves into the central Arctic Ocean. Chukchi shelf sediments were important sources of dCd, dZn, and dNi, as well as marine ligands that bind and carry these TEs offshore within the upper halocline in the Canada Basin. Our data suggest that tDOM components represent stronger ligands relative to marine DOM components, potentially facilitating the long‐range transport of TE to the North Atlantic. Plain Language Summary: The Arctic Ocean receives a disproportionate large amount of global river discharge and has limited but well‐constrained exchanges with other oceans. This makes the Arctic Ocean unique in terms of dissolved organic matter (DOM) and trace element (TE) sources and distribution. We used data collected during two expeditions spanning the entire Arctic Ocean to characterize the unique distribution of DOM and to study its potential as a water mass tracer and its role in the transport of TE. While the Atlantic‐dominated Nansen Basin was characterized by low levels of the DOM and TE, the central Arctic was dominated by the Transpolar Drift, a current that connects the Eurasian shelves to the Fram Strait and transports DOM from the Siberian Rivers toward the North Atlantic. In contrast, the Chukchi shelf‐Canada Basin region was characterized by the dominance of Pacific water that is enriched by marine DOM from the shallow and productive Chukchi shelf. The distribution of DOM from these different sources was affected by freezing and thawing processes and, therefore, can be used to study water mass transformations and pathways in the Arctic Ocean. Key Points: Dissolved Organic Matter (DOM) distribution in the Arctic Ocean is largely controlled by sea ice formation and melt processes DOM distribution in the Arctic Ocean reveals its potential as a tracer for halocline formation and freshwater source assignments Terrigenous and marine DOM are carriers of trace elements from shelves to the open Arctic Ocean, but terrigenous DOM represent stronger ligands